Elements of ecology - Smith, T. M. (Thomas Michael) 1955- (San Francisco Pearson, 2015)
An introductory textbook for college students.
The nature of ecology -- Climate -- The aquatic environment -- The terrestrial environment -- Adaptation and natural selection -- Plant adaptations to the environment -- Animal adaptations to the environment -- Properties of populations -- Population growth -- Life history -- Intraspecific population regulation -- Species interactions, population dynamics, and natural selection -- Interspecific competition -- Predation -- Parasitism and mutualism -- Community structure -- Factors influencing the structure of communities -- Community dynamics -- Landscape dynamics -- Ecosystem energetics -- Decomposition and nutrient cycling -- Biogeochemical cycles -- Terrestrial ecosystems -- Aquatic ecosystems -- Coastal and wetland ecosystems -- Large-scale patterns of biological diversity -- The ecology of climate change.
Keywords: Ecology; Ecology -- Textbooks; Ecology -- Study and teaching (Higher)